FACTORS THAT INFLUENCE FINANCIAL STATEMENT FRAUD AND FINANCIAL DISTRESS: AN INVESTIGATION STUDY - Sanjayyana, Adzka Rosa; Urumsah, Dekar (APSSAI ACCOUNTING REVIEW, 2021)
This study aims to analyze the factors of the Fraud Diamond Theory, Change in Auditor, Capability, Financial Targets, External Pressure, and Ineffective Monitoring in the occurrence of Financial Statements Fraud and Financial Distress. Using logistic regression analysis method to test the data, the results showed that External Pressure affected Financial Statements Fraud and Financial Targets affected Financial Distress. Meanwhile, Change in Auditor, Capabilities, Financial Targets, and Ineffective Monitoring had no effects on Financial Statements Fraud and External Pressures had no effects on Financial Distress. In addition, when Financial Distress was connected with Financial Statements Fraud, the result of the study showed that there was no influence between Financial Distress and Financial Statements Fraud. Thus, it is advisable that auditors, investors, creditors, and management work in synergy with each other in preventing and protecting from the occurrence of financial statement fraud by observing the indicators which trigger fraud in a company.